Studi Empiris Pengaruh Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Ch Jeffry Pradana; Edy Liswani; Eni Cahyani (Universitas Veteran Bangun Nusantara, 2025)
The purpose of this study was to determine the effect of Work Motivation, Work Discipline, and Work Environment on Employee Performance at AJB Bumiputra Palembang Regional Office simultaneously and partially. This type of research is associative research. The population is limited and the sample is 41 respondents. The data used are Primary and Secondary data, using questionnaire and observation data collection methods. The analysis techniques used are Multiple Linear Regression, F and T Hypothesis Tests, and the Coefficient of Determination. The study results indicate a positive effect of Work Motivation, Work Discipline, and Work Environment on Employee Performance at AJB Bumiputera 1912 Palembang Regional Office.